Pharmacogenomics in Cardiovascular Diseases. Issue 7 (7th July 2021) - McDonough, Caitrin W.
Abstract: Cardiovascular pharmacogenomics is the study and identification of genomic markers that are associated with variability in cardiovascular drug response, cardiovascular drug−related outcomes, or cardiovascular drug−related adverse events. This overview presents an introduction and historical background to cardiovascular pharmacogenomics, and a protocol for designing a cardiovascular pharmacogenomics study. Important considerations are also included for constructing a cardiovascular pharmacogenomics phenotype, designing the replication or validation strategy, common statistical approaches, and how to put the results in context with the cardiovascular drug or cardiovascular disease under investigation. © 2021 Wiley Periodicals LLC. Basic Protocol : Designing a cardiovascular pharmacogenomics study